Educação profissional brasileira: Análises, discussões e tendências - Stênico, Joselaine Andréia de Godoy [UNESP]; e Silva, Joyce Mary Adam de Paula [UNESP] (My University, 2014)
This research is devoted to analyzing the vocational education in the context of Brazilian society. Initially, we present a mapping that allows unravel and examine the knowledge already elaborated on vocational education. The developed analyzes focused on demonstrating the most relevant aspects that studies have treated to demonstrate the scientific knowledge on the subject, highlighting objects and preferred approaches given to these objects. Subsequently, we present our analysis and discussions to identify possible contributions of research towards social disruption.The investigation took a qualitative approach, guided by the Bibliographic Search and search by the type State of the Art. Among the main results, it is worth highlighting the emphasis on respect basic education - vocational education, for the treatment of the subject with the relevant legislation, as well as the incidence of competence and qualification terms in discussions of professional education.This ideology has been absorbed by educational and broadly disseminated proposals in educational practices, reflected in the school curriculum that increasingly turns to the context of the working world though not directly, but providing that knowledge to be included in educational practice allow better matching the needs of the youth market.
Brazilian professional education: Analysis, discussion and trends
Keywords: Competence and skills; Education and manpower; Profissional education